Pengaruh Penempatan Dan Disiplin Kerja Terhadap Kinerja Pegawai Badan Pertanahan Kota Bima - Nurkhalisa Nurkhalisa; Amirulmukminin Amirulmukminin (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
In a bureaucratic government system, human resources are basic capital, or play an important role in achieving organizational goals. Therefore, organizations need to manage and develop human resources well. One of the main functions of government is to provide public services as a manifestation of the government's general duties for the welfare of society. Bureaucracy is a government instrument to create public services that are efficient and effective, fair, transparent and accountable. This means that to be able to carry out government functions well, bureaucratic organizations must be professional, responsive, aspirational, to the demands of society.